2014
DOI: 10.2337/db14-0342
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Integrity Disruptions Associated With Cognitive Impairments in Type 2 Diabetic Patients

Abstract: Type 2 diabetes mellitus (T2DM) is associated with a twofold increased risk of dementia and can affect many cognitive abilities, but its underlying cause is still unclear. In this study, we used a combination of a battery of neuropsychological tests and diffusion tensor imaging (DTI) to explore how T2DM affects white matter (WM) integrity and cognition in 38 T2DM patients and 34 age-, sex-, and education-matched normal control subjects. A battery of neuropsychological tests was used to assess a wide range of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
93
4
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(120 citation statements)
references
References 47 publications
20
93
4
3
Order By: Relevance
“…We found similar results from Reijmer et al's study that WMN parameters were associated with worse cognitive performances in patients with T2DM [12]. Besides, studies in T2DM patients showed that executive function impairment was related to WM integrity decline including internal and external capsules [7]. These findings also support the idea that the decreased nodal efficiency of ROL connects with executive function impairment in T2DM patients.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We found similar results from Reijmer et al's study that WMN parameters were associated with worse cognitive performances in patients with T2DM [12]. Besides, studies in T2DM patients showed that executive function impairment was related to WM integrity decline including internal and external capsules [7]. These findings also support the idea that the decreased nodal efficiency of ROL connects with executive function impairment in T2DM patients.…”
Section: Discussionsupporting
confidence: 80%
“…These abnormal phenomena maybe attributed to reduced WM integrity and increased disconnection; some microvascular lesions and enlarged perivascular spaces would induce possible neuropathology changes in T2DM [30]. Previous studies provide direct evidence for disrupted structural integrity in various WM tracts in diabetic patients, such as the corpus callosum [7,31]. Overall, our findings provide additional evidence for the imbalanced topological organizations and reduced efficiency for signal propagation in patients with diabetes.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Studies on middleaged adults with cognitive complaints also have shown that lower activation in the SFG is related to poorer WM performance (42). Moreover, in light of recent white matter studies, increased impairments in the frontal fiber tracts were associated with reduced executive function (43) and information processing speed (16) in T2DM patients. Demyelination of axons, loss of glial cells, expanded microvascular lesions, enlarged perivascular spaces, and even bloodbrain barrier disruptions possibly induce neuropathological changes in brain structure and function in T2DM patients (44).…”
Section: Discussionmentioning
confidence: 99%
“…Structural MRI studies on T2DM have revealed the aberrant hyperintensity in the thalamus associated with impaired speed of mental processes and memory (Akisaki et al 2006). Zhang et al reported decreased fractional anisotropy and increased mean diffusivity in widespread WM tracts in T2DM compared with controls, including the posterior thalamic radiation (Zhang et al 2014). Furthermore, impaired macromolecular protein pools in fronto-striato-thalamic circuits were demonstrated in T2DM using magnetization transfer imaging (Yang et al 2014).…”
Section: Introductionmentioning
confidence: 96%